Political Attitudes in the Literary Works of Mahmoud Saif Al-Din Al-Irani - Al-Hajjajah, Bashir Aqab; Al-Salamat, Atef Abdul-Karim (Journal of Humanities & Social Sciences, 2020)
The research seeks to reveal the most important political attitudes presented by the writer (Mahmoud Saif Al-Din Al-Irani) in his literary works - other than those that critics have shown in his works before - and that were reached after research and reading in a number of his literary stories, and his political articles, especially those The stories that talk about (Jaffa) the city in which (Al-Irani) was born and lived the moments of childhood, as well as stories that show the memories of the homeland and depict the pain of its people and their struggle against the brutal Jewish occupation of their cities and villages. After identifying these positions, they were presented, discussed, and presented supporting evidence and evidence supporting them from Al-Irani stories and literary articles.